2013
DOI: 10.1002/jca.21256
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for utilizing peripheral blood CD34 count as a predictor of the need for plerixafor in autologous stem cell mobilization—cost‐effectiveness analysis

Abstract: Certain patients who receive granulocyte colony-stimulating factor (GCSF) for autologous hematopoietic stem cell (AHSC) collection fail to mobilize well enough to proceed with transplant. When plerixafor is used with GCSF, the likelihood of achieving the CD34⁺ stem cell target in fewer collections is higher; plerixafor use in all patients is unlikely to be cost-effective. This study retrospectively evaluated the effectiveness of utilizing a peripheral blood CD34⁺ stem cell count (PBCD34) ≤8/µL on day 4 of GCSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Whether plerixafor is cost-effective depends on the selected perspective, as well as on fees and procedures, specific to each institution [21,[24][25][26]. Studies adopting a wider perspective which captures additional costs incurred to the hospital due to mobilization failure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Whether plerixafor is cost-effective depends on the selected perspective, as well as on fees and procedures, specific to each institution [21,[24][25][26]. Studies adopting a wider perspective which captures additional costs incurred to the hospital due to mobilization failure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the average number of CD34+ cell collection was also reported in other studies: Micallef et al reported an increase in the median CD34+ cell collection from 5.6 × 10 6 CD34+/kg without plerixafor to 7.8 × 10 6 CD34+/kg with plerixafor . On the other hand, Abusin et al reported no statistically significant difference between the final CD34+ cumulative yield between two cohorts treated prior or after plerixafor introduction . Such differences could be due to different treatment algorithm, apheresis procedures, or differences in underlying disease distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have published results regarding the additional cost related to the use of plerixafor under different protocols. These costs depend on local fees and prices as well as the perspective adopted in the costing analysis; however, most studies concluded that the use of plerixafor led to an additional but acceptable cost, given the clinical benefit obtained . Micallef et al reported a higher variability in costs in patients treated with G‐CSF only.…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to assess the extent to which plerixafor might have altered clinical outcome or not (e.g., overall or relapse free survival), since patients were not routinely followed beyond 12 months after their transplant. The analysis is therefore a cost‐effectiveness study (cost per patient achieving a stem cell yield sufficient to support a subsequent transplant), and contributes to the increasing evidence about the cost‐effectiveness of plerixafor in myeloma and lymphoma patients .…”
Section: Methodsmentioning
confidence: 99%